Replication and transmission features of two experimental vaccine candidates against bovine tuberculosis subcutaneously administrated in a murine model - Ferrara Muñiz, Ximena; Garcia, Elizabeth Andrea; Blanco, Federico Carlos; Bigi, Fabiana; Zumarraga, Martin Jose; Cataldi, Angel Adrian; Eirin, Maria Emilia (Elsevier, 2022)
Cattle vaccination is an attractive approach in compliance with control and eradication programs against Bovine Tuberculosis (bTB). Today, there is no anti bTB vaccine licensed. Two vaccine candidates, MbΔmce2 and MbΔmce2-phoP previously designed were evaluated in BALB/c mice, including the parental M. bovis NCTC10772 and a M. bovis hypervirulent Mb04-303 strains as controls. Sentinel mice (non-inoculated) cohoused with subcutaneous inoculated mice. Persistence, visible tuberculosis lesions (VTL) in lungs and spleens and bacillary load were investigated subcutaneously delivered at 60 and 90 days after inoculation (dpi) as well as their potential transmission to naïve mice.